Turnaround and failure: resource weaknesses and the rise and fall of Jarvis - Wild, Andrew; Locket, Andrew (Taylor and Francis, 2015)
Research employing the resource-based view (RBV) has overwhelming focused on the upside of resources, namely those that provide benefit to the firm. However, an emerging research stream suggests that the downside of resources, namely resource weaknesses, may be crucial in gaining a greater understanding of the key factors that contribute to firm performance and the ability to turnaround failing companies. We examine the infamous case of Jarvis, a firm that achieved a turnaround, but then experienced catastrophic failure. In so doing we explore the emergence of resource weaknesses, their nature and ability to combine to create a fatal organisational outcome.